Simulation of a microjet array cooling system - Mohd. Ghazali, Normah (Penerbit UTM, 2007)
As the power density increases in line with more powerful microchip, the power dissipation for high performance processor is expected to go up. With more transistors to be fitted into the microchip, the extraordinary high heat dissipation generated at hotspots will cause a sharp increase of the local temperature, which will damage the microchip. The finned and metallic type heat sink can remove heat from the hot surface uniformly, but the extra heat from the hotspots will not be removed efficiently. With the dimensions expected to remain at 310 mm 2 and the junction temperature at 85°C (Copeland, 2005), the heat density may well approaches the limit of conventional cooling methods. The study on microjet arrays has just begun in the recent years. The escalating demand over the years for a faster microchip, higher computing power and greater functionality, has increased the power density just as the length scales have been reduced. Microchannel heat sink in microchip cooling has been widely use since the 1980’s.